Centro cultural na zona norte de Macapá: a cultura como meio de integração - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2018)
This work has the general objective of elaborating a proposal for the architectural design of a Cultural Center in the neighborhood of Jardim Felicidade, Zona Norte de Macapá, in order to provide leisure, culture and entertainment to the residents of the city in a regional access range, with a view to deficiency of this type of building in this part of the city. The work starts from the premise of the need to insert socio-cultural activities and leisure activities, enabling the production of culture, combined with the creation of jobs. For the purpose of research, the CEU of the Arts of the neighborhood Infraero II, implanted in the Norde Macapá Zone, will be analyzed through a methodology of Post-Occupancy Assessment - APO - aiming to subsidize the Cultural Center project through the locus analysis of the characteristics of this Center Which today includes Culture, sports, leisure, entertainment and social services promoted by the Macapá's prefecture. The main motivation of this proposal is to value access to culture, creating a place where activities are centralized, both in exhibitions, lectures, workshops, and in corresponding events, and in this way create a culture attracting pole, not only because it is proposed in the North Zone as also covering the metropolis since there is a shortage of cultural spaces in Macapá Capital.
Keywords: Avaliação pós-ocupação; CEU das Artes - Macapá (AP); CNPQ::CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO